Analysis of the Problems of Gender Equality Before God - Fitri Nur Adinda; Irzum Farihah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2024)
Gender inequality is not solely a social issue; it extends to economic, cultural, political, and scientific dimensions, often compounded by misinterpretations of religious texts. This research arises from the author’s concern regarding the marginalization of women, often perceived as second-class citizens in patriarchal societies. This concern is explored through the lens of gender equality issues depicted in the novel “Perempuan yang Memesan Takdir”. The study aims to analyze the novel and present descriptive findings on various forms of gender injustice, employing a religious perspective grounded in gender equality theory and the concept of mubadalah. The research adopts a content analysis method to interpret the findings within the novel. These findings are categorized into five forms of gender injustice: marginalization, subordination, stereotyping, violence, and the imposition of double workloads. The results reveal that gender inequality stems from three main factors: (1) power dynamics and social stratification that restrict women in multiple domains, (2) cultural and traditional practices that perpetuate patriarchal values, and (3) societal structures that hinder the realization of gender equality.